Introduction to porous materials - Van Der Voort, Pascal Laurent Jules 1967-; Leus, Karen 1985-; Canck, Els de 1985- (Inorganic chemistry, 2019)
The first comprehensive textbook on the timely and rapidly developing topic of inorganic porous materialsThis is the first textbook to completely cover a broad range of inorganic porous materials. It introduces the reader to the development of functional porous inorganic materials, from the synthetic zeolites in the 50's, to today's hybrid materials such as metal-organic frameworks (MOFs), covalent organic frameworks (COFs) and related networks. It also provides the necessary background to understand how porous materials are organized, characterized, and applied in adsorption, catalysis, and many other domains.